The Role of Sulfur Amino Acids in Risk of Kwashiorkor - Fitzpatrick, Merry Colleen. (2018)
Abstract: Abstract Kwashiorkor is a form of severe acute malnutrition identified more than 80 years ago as a syndrome and still affects hundreds of thousands of children each year, yet its etiology remains unknown. A better understanding of its etiology is necessary to develop effective preventive strategies. Although kwashiorkor is only found in regions where protein intake and sanitation are poor, study findings comparing the dietary protein intake of children with and without kwashiorkor have been conflicting. Protein quality has not been explored and the large array of signs characterizing kwashiorkor can plausibly be explained by a deficiency of sulfur amino acids (SAAs). Children with kwashiorkor have low circulating sulfur amino acids (methionine and cysteine) and their metabolites, and their metabolism of SAAs is altered. The aim of this research is to provide evidence upon which to design preventive interventions, hypothesizing that children in higher-prevalence populations will have lower intakes of SAAs, and that low intake of SAAs will be a stronger predictor of the risk of kwashiorkor than other factors. Additionally, due to its low nutrient content and potentially high cyanide content, cassava intake was hypothesized to be a stronger predictor of risk than food security. An anthropometric survey of all children in one Health Area of eastern Democratic Republic of the Congo located all cases of kwashiorkor among children 12 to 59 months old to aid in the selection of two populations with very different prevalence. A commercial laboratory was used to provide amino acid profiles on market samples of key staples and sources of proteins. Household samples of cassava flour and cooked cassava leaves were tested for cyanogens. Interviews with caregivers of children 36 to 59 months old recorded multiple factors of the household and the child and a 24-hour quantitative recall of the child's diet. Among the many signs characterizing kwashiorkor, only bipedal pitting edema is used for admission to treatment, though light-colored brittle hair and facial edema have been reported to appear before edema in the feet, therefore all visible signs were recorded. One urine sample was taken to compare urinary sulfate and another for thiocyanate. Analysis included GIS mapping, direct statistical comparisons of diets, and path analysis modeling of the multiple potential causal factors. Together, the findings showed children in a population with a higher prevalence of kwashiorkor had lower intakes of sulfur amino acids, methionine in particular, more children in this population were at risk of inadequate methionine intake than other amino acids, and methionine was the limiting amino acid in both populations. Median intake of both methionine and cysteine was above the WHO requirement, but true adequacy of a nutrient must take into consideration factors that raise the requirement. Children in the HPP were more stunted, were ill more often, and their families were more food insecure than those in a lower-prevalence population. SAA intake, followed by illness, was the strongest predictor of a family history of kwashiorkor. A family history of kwashiorkor, followed by illness, was the strongest predictor of early signs of kwashiorkor. It appears that low SAA intake makes children especially vulnerable to kwashiorkor, but illness is often the event that triggers the onset of the syndrome. Intervention trials to reduce prevalence of kwashiorkor should simultaneously reduce exposure to infection and increase intake of both cysteine and methionine.; Thesis (Ph.D.)--Tufts University, 2018.; Submitted to the Dept. of Food Policy & Applied Nutrition.; Advisor: Daniel Maxwell.; Committee: Shibani Ghosh, Anura Kurpad, and Christopher Duggan.; Keywords: Nutrition, Public health, and Epidemiology.